Level of physical fitness taekwondo UKM students - Ardhika Falaahudin; Ayub Tatya Admaja; Dody Tri Iwandana (Nicolaus Copernicus University in Toruń, 2020)
All Taekwondo UKM students are required to have good physical fitness. Because the exercise contains a lot of physical elements, so Taekwondo UKM students are required to have good stamina and fitness. One example of activities that are mandatory and cannot be refused by students is running. The purpose of this study was to determine the level of physical fitness of male taekwondo UKM students at Mercu Buana University Yogyakarta. This research is a descriptive study, in this study the researcher only wants to describe the current situation without testing the hypothesis. The instrument and data collection technique used was a 12-minute running test from Kenneth Cooper. The data obtained are then converted to the Kennet Cooper table to find out the category of physical fitness level. Data result VO2Max UKM Taekwondo Mercubuana Yogyakarta is classified as sufficient criteria / kateogri with an average value of 39.5. While the lowest value is 32.3 and the best value is 51.3. With the known VO2 Max status, it can be concluded that the physical condition of UMBY Taekwondo UKM members is sufficient, and still needs to be improved.